Sliding and Lower Limb Mechanics during Sit-Stand-Sit Transitions with a Standing Wheelchair. (6th July 2014) - Yang, Yu-Sheng; Chen, Ming-De; Fang, Wei-Chien; Chang, Jyh-Jong; Kuo, Chang-Chih
Abstract : Purpose. This study aimed to investigate the shear displacement between the body and backrest/seat, range of motion (ROM), and force acting on the lower limb joints during sit-stand-sit transitions by operating an electric-powered standing wheelchair. Methods and Materials. The amounts of sliding along the backrest and the seat plane, ROM of lower limb joints, and force acting on the knee/foot were measured in twenty-four people with paraplegia. Results. Without an antishear mechanism, the shear displacement was approximately 9 cm between the user's body and the backrest/seat surfaces. During standing up, the user's back slid down and the thigh was displaced rearward, but they moved in opposite directions when wheelchair sat back down. A minimum of 60 degrees of ROM at the hip and knee was needed during sit-stand-sit transitions. The maximal resultant forces acting on the knee restraints could reach 23.5% of body weight. Conclusion. Sliding between the body and backrest/seat occurred while transitioning from sitting to standing and vice versa. A certain amount of ROM at lower limb joints and force acting on the knee was necessitated during sit-stand-sit transitions. Careful consideration needs to be given to who the user of the electric powered standing wheelchair is.